Diversity in life types of spider mites - Saito, Yutaka; Sato, Yukie (Frontiers in Arachnid Science, 2024)
Phytophagous spider mites, belonging to the subfamily Tetranychinae, have diverse lifestyles. Life type is an important concept for understanding spider mite diversity. There are three basic life types: little web (LW), non-systematic and complicated web (CW), and woven nest (WN), which are characterised by silk production, silk usage patterns, faeces defaecation patterns, and other behavioural outcomes. In this review, we first address the diversity of life types and then discuss the functions of life types as reported by several studies. The primary function of the CW type is to provide a firm footing for residing on the underside of host leaves and to protect mites from the deleterious effects of solar radiation. Next, we discuss how spider mites have evolved various defence mechanisms through life types to avoid their natural enemies. We observed that the life type can affect the results of interspecies competition. Faeces manipulation behaviours observed in the CW and WN type mites may be an adaptation to keep a clean habitat. The CW species showed a significantly higher intrinsic rate of natural increase (rm) than LW and WN species, and such differences may be associated with host plant stability.Although there was no apparent relationship between sex ratio and life type, the extremely female-biased sex ratio in several WN species appears to contribute to local mate competition. In contrast, WNs strongly affect the aggressiveness of males because they provide a recognisable domain that they should defend. Furthermore, the WN type enhances mite aggregation in nests, and their iteroparous reproduction causes generation overlapping. Such traits may lead some WN species to develop advanced sub-sociality (cooperative sociality).